"Local peoples'" and "visitors'" views on infrastructure and services in protected areas: a case study from Evros, Greece. (1st January 2013) - Andrea, Veronika; Tampakis, Stilianos; Tsantopoulos, Georgios; Skanavis, Constantina
This case study attempts to explore "local peoples'" and "visitors'" views about the existing infrastructure and the availability of the services of the two National Parks of Evros Prefecture. The purpose of the research is to find out any potential deficiencies which might be influencing "local peoples'" lives and "visitors'" travel experience. The sustainable use of natural resources and tourism are crucial in the management of protected areas and National Parks. Sustainable development in such areas can only be achieved if the tourism infrastructure and related services are effectively managed. The results showed that local people are deemed to be stricter in their assessment of the existing infrastructure and services provided compared to the visitors in both areas. Although the structures of the tours and activities in the two National Parks are not similar, there were significant similarities in the visitors' perceptions in both scenarios.